TUJUAN TIONGKOK MENEMPATKAN ANJUNGAN MINYAK HYSY 981 DI AREA PERSENGKETAAN LAUTAN BARAT PARACEL - Mannakari, Zaib Zakaria; Kumala Dewi, Putu Ratih; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2021)
This research aims to explain the purpose of China’s decision to deploy the HYSY 981 oil rig on the contested waters of the Paracel Islands on 2014, using qualitative research methods. The theoretical framework used in this research consists of geopolitics theory and the concept of power projection. Policies are made to fulfill a state’s goal in accordance to Geopolitics, which is territorial expansion. To achieve this, China made a policy to project their power towards the Paracel Islands. However, China faces sustainability issues. This research then concludes that China’s purpose behind their decision on placing the HYSY 981 rig on the contested waters is to establish a reliable energy field for their power projection in the Paracels. The establishment of a reliable energy field would solve the sustainability issue that China is facing in projecting their military power towards the Paracel Islands.   Keywords: China, Vietnam, HYSY 981 Rig, Power Projection